Selective defaunation affects dung beetle communities in continuous Atlantic rainforest - Culot, Laurence [UNESP]; Bovy, Emilie [UNESP]; Zagury Vaz-de-Mello, Fernando; Guevara, Roger; Galetti, Mauro [UNESP] (Elsevier, 2013)
Overhunting has caused severe decline or local extinction in many large-bodied mammals with direct consequences on plant regeneration, yet little is known about indirect impacts of selective defaunation on commensal species. Cascading effects of species extinction across dependent species groups are likely to occur in coprophagous beetles, because these invertebrates rely on mammal dung for food and nesting material. Both mammals and dung beetles provide important ecosystem services and cascading effects are likely to lead to rapid functional losses. In this study, we described changes in dung beetle communities across a gradient of selective defaunation in continuous Brazilian Atlantic rain forest. We compared the dung beetle assemblages in seven sites with different mammalian biomass and composition. The reduction in the mammalian biomass had a major effect on dung beetle communities by (1) increasing dung beetle abundance with decreasing overall mammal, primate and large mammal biomasses, (2) decreasing dung beetle species richness with decreasing overall mammal biomass and (3) decreasing dung beetle size with decreasing large mammal biomass. Moreover, our study demonstrated the importance of the composition of mammal communities in structuring dung beetle communities. This study documented how selective changes in mammalian biomass and composition affect dung beetle species communities, which in turn may have cascading consequences for the ecosystem. Since most of tropical ecosystems are facing dramatic changes in mammalian composition, it is urgent to evaluate the functional losses associated with such co-extinctions. © 2013 Elsevier Ltd.
Keywords: Dung beetle species richness; Hunting; Mammal biomass; Mammal composition; Trophic cascades; beetle; ecosystem service; hunting; local extinction; mammal; population decline; rainforest; species richness; trophic cascade; Atlantic Forest; Brazil; Coleoptera; Invertebrata; Mammalia; Primates